Partisipasi Masyarakat Dalam Mitigasi Abrasi Pantai Imbuti Kabupaten Merauke - Purnama, Erwin Nugraha; Saragih, Dapot Pardamean; Sari, Puspita Wulan (Jurnal Administrasi Karya Dharma, 2025)
Coastal abrasion is a significant environmental threat that endangers both the ecological stability of coastal areas and the socio-economic conditions of communities in Merauke Regency, including those living around Imbuti Beach. This study aims to describe the level, forms, and dynamics of community participation in coastal abrasion mitigation at Imbuti Beach. Using a qualitative approach grounded in post-positivist philosophy and a descriptive research method, data were collected through field observations, in-depth interviews, and document analysis. The analysis employed participation indicators proposed by Huraerah (2011), which include participation in planning, implementation, and material contribution. The findings indicate that community participation remains relatively low across all indicators. Limited public understanding of the causes of abrasion, low ecological awareness, and heavy reliance on government intervention are the primary factors contributing to weak local initiatives in mitigation efforts. Additionally, practices such as sand mining and residential development beyond the designated coastal buffer zone have exacerbated environmental degradation in the area. These findings highlight the need to strengthen community capacity, enhance environmental education, and establish community-based coastal governance mechanisms as strategic efforts to encourage active participation in protecting and restoring the Imbuti Beach ecosystem.